Impact of Capital Market on GDP Growth in Nepal (The Lumbini Journal of Business and Economics, 2023)
This study explores the connection between the capital market and Nepal's GDP growth from 1994 to 2002. The study examines how capital market performance affects the GDP growth of Nepal. The ARDL approach was used to examine the capital market's long-term effect on economic growth. To this extent, variables like market capitalization, gross fixed capital formation as investment, broad money supply, the NEPSE Index, the number of listed companies in NEPSE, and recurring expenditures were used in the system, affecting GDP growth. According to the study,  the correlation shows the presence of a strong linkage between the capital market and GDP growth in Nepal. Findings show that the capital market has a significant influence on GDP growth. Negative and significant error correction terms indicate how quickly shocks and equilibrium are corrected. Some of the variables are insignificant in the short and long run, indicating the presence of structural and institutional lacks in Nepal's capital markets.